ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI KONSUMSI KOPI DAN ANALISIS PEMETAAN BEBERAPA MEREK KOPI DAN IMPLIKASINYA PADA PEMASARAN KOPI - Wahyudian Wahyudian; Ujang Sumarwan; Hartoyo Hartoyo (Jurnal Manajemen & Agribisnis, 2004)
The purpose of thisstudy was to identify the influencing factors of consumer decision's process tobuy and consume coffe, and to analyze consumer perceptual by attributes.. Thedata were analyze from 190 respondents in Jakarta.Linear regresion and biplot were used to analyze the data. The results ofregression analyses showed that younger respondents aged between 18 to 25 yearsold had higher probability to consume coffee that that of older respondents.Respondents who perceived having some deseases also had lower probability toconsume coffee. Analyses of perceptual mapping showed that Nescafe and indocafewere located in the same quadrant, indicating that these two coffee brands werepereceived to be similar by respondents. Indocafe was also associated with theattribute of good smell and good packaging , whereas Nescafe was close relatedto the attributes of popularity in advertising in mass media.The results of thestudy suggested for marketing implications that coffee producers should makemarket penetration strategy by age and sex. Producers can produce coffee withother variant or coffee without caffeine, Sachet is still usable because itspractical, preserve the taste and the smell of the coffee.